The impact of risk perception on the purchase intention among Generation X on autonomous vehicle in Malaysia. - Teng, Wen Hao; Ang, Jia Hui (2024)
As acceptance of autonomous vehicles is developing in Malaysia, it has been noted that many Generation-Xs have had challenges in attempting the technology when controlling an autonomous vehicle is a hassle to them. As a result, this study is to figure out the factors that affect the Generation X intention in adopting the technology of autonomous vehicle. From the literature review, the Perceived Risk Theory of Bauer (1960) and few other variables that might affect Generation Xs’ tendency to purchase autonomous vehicles have been utilised to formulate hypotheses and to gain knowledge of purchase intention to achieve the purpose of the study. The data were gaining from Generation X respondents through researcher assisted electronic questionnaire survey by using PAD. A total of 370 completed data were recorded and they were examined and analysed by using SPSS and SmartPLS software. The analyses found that there were negative relationships between PR and PH with trust whereas PH didn’t show any significant relationship with trust. The constructs of SO and FI shown significant negative relationships with PI but PR and PH didn’t show any significant value whereas FU shown positive relationship with PI and therefore two relationships were supported and three relationships were not supported. Further, TR shown significant mediation effect on the relationship between PR and PI and between FU and PI but not between PH and PI. As a conclusion, this study found some significant relationships between perceived risks with PI of autonomous vehicle and there are some perceived risks that do not have such effect. Similarly, same kind of findings also occur on the relationships between three perceived risks and TR. This study would be a key reference for academics, industrial practitioners and government in research, in implementing business strategy and in policy formulation. Limitation and further research suggestions were also provided. KEYWORDS • RISK PERCEPTION • AUTONOMOUS VEHICLE • GEN-X • PURCHASE INTENTION • TRUST SUBJECT AREA • TL1-484 MOTOR VEHICLES. CYCLES